Numerical Analysis of Header Structure Improvement in a Plate‐Fin Heat Exchanger. Issue 10 (16th June 2016) - Zhang, Bing; Fan, Gang; Yang, Jian; Liu, Chuangui; Tang, Shan
Abstract: In order to improve the flow uniformity in a plate‐fin heat exchanger (PFHE), a modified header structure with a plain baffle inside is proposed. Flow distribution and pressure drop in the header were studied by numerical methods. The results show that the modified header is highly efficient in improving the flow uniformity with negligible pressure drop increase. A performance effectiveness factor was introduced to predict the effects of the modified structure on the performance of the PFHE. Influences of baffle structure parameters on modified structure performances were further discussed. The modified header structure can effectively improve the performance of a PFHE. Abstract : An innovative header structure with a plain baffle inside for improving the flow uniformity of plate‐fin heat exchangers is proposed. Flow distribution and pressure drop characteristics in conventional and modified headers of heat exchangers are compared. A performance effectiveness factor is introduced to predict the effects of the proposed structure.